El circuito de los afectos. Cuerpos políticos, desamparo y el fin del individuo - Safatle, Vladimir (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2019)
We must always bear in mind that certain forms of life are based on specific affects. That is to say, they need these affects to continue to repeat themselves, to impose their modes of ordering, thus defining the field of the possible. There is a social adhesion that is constructed through affects. In this sense, when societies are transformed, they open up to the production of singular forms of life and, in this sense, affects begin to circulate in a different way, to be agenticulated in such a way that other objects and effects are produced.